Thō̜ngkham thī chai nai kānbūrana patisangkhō̜n plī yō̜t thō̜ngkham Phrabō̜rommathāt Čhēdī Nakhō̜n Sī Thammarāt, Wat Phramahāthāt Wō̜ramahāwihān, ʻAmphœ̄ Mư̄ang, Čhangwat Nakhō̜n Sī Thammarāt rawāng Phutthasakkarāt 2537-2538 : ʻanusō̜n nai kānphrarātchathān phlœ̄ng sop Nāi Nopphawat (Sanan) Somphư̄n, Mō̜. Wō̜. Mō̜., Pō̜. Chō̜., na mēru Wat Makutkasattriyārām, Khēt Phra Nakhō̜n, Krung Thēp Mahā Nakhō̜n, Wančhan thī 16 Phrưtsaphākhom, Phō̜. Sō̜. 2548 - Nopphawat Somphư̄n; Yongyut Wannakōwit (s.n., 2005)
On the use of gold in the reconstruction of Phrabō̜rommathāt Čhēdī Nakhō̜n Sī Thammarāt of Wat Phramahāthāt Wō̜ramahāwihān in Nakhon Si Thammarat Province, Thailand; published as a cremation volume for Nopphawat (Sanan) Somphư̄n of Thailand's Fine Arts Department and includes his biography and condolences.